Circulating Concentrations of Adipocytokines and Their Receptors in the Isolated Corpus Cavernosum and Femoral Artery from Trained Rats on a High-Fat Diet - Sponton, Amanda C.S.; Silva, Fábio H.; Araujo, Hygor N.; Valgas Da Silva, Carmem P. [UNESP]; De Moraes, Camila; Antunes, Edson; Zanesco, Angelina; Delbin, Maria A. (Karger Publishers, 2017)
Background: The aim of the present study was to evaluate different signaling pathways by which exercise training would interfere in endothelial function in obesity. Therefore, we examined adipocytokine levels and their receptors in the corpus cavernosum and femoral artery from trained rats on a high-fat diet. Methods: Functional experiments were performed in control sedentary and trained rats, and sedentary (h-SD) and trained male Wistar rats on a high-fat diet (h-TR). Nitric oxide (NO) and reactive oxygen species (ROS) were evaluated in vascular tissue. Circulating adipocytokines and their receptors were analyzed. Results: In the h-SD group, the maximal responses to acetylcholine (ACh) were reduced in the femoral artery and corpus cavernosum as well as the electrical field stimulation, accompanied by an increase in circulating insulin, leptin, TNF-α, MCP-1, and PAI-1. Downregulation of ObR protein expression in the femoral artery was observed without alterations in AdipoR1 and TNFR1 in both preparations. A positive effect was observed in the h-TR group regarding the relaxation response to ACh and circulating adipocytokines, resulting in increased NO production and reduced ROS generation. Exercise restored the ObR protein expression only in the femoral artery. Conclusion: Aerobic exercise training ameliorated the inflammatory adipocytokines and restored the relaxation responses in the corpus cavernosum and femoral artery in rats on a high-fat diet.
Keywords: Adipocytokines; Aerobic exercise; Corpus cavernosum; Endothelial dysfunction; Femoral artery; High-fat diet